EDUKASI ASPEK LINGKUNGAN PENYEBAB STUNTING DI WILAYAH KERJA PUSKESMAS REJOSARI - Eliza Fitria; Carles Carles; Betty Nia Rulen (Ensiklopedia Research and Community Service Review, 2025)
Stunting remains a serious public health issue in Indonesia, particularly among children aged 0–59 months, a critical period for growth and development. Based on data from the Pekanbaru City Health Office, Rejosari Public Health Center has consistently reported a high prevalence of stunting over the past three years. One of the key contributing factors to stunting is poor environmental sanitation. This community service program aimed to increase knowledge and awareness among mothers of toddlers about environmental factors that cause stunting and how to prevent it through community-based sanitation education. The method involved health education through leaflets, posters, lectures, and interactive demonstrations. The participants were 15 mothers of toddlers living in the Rejosari health center area. Evaluation was conducted using pre-tests and post-tests to measure changes in knowledge. Results showed a significant improvement in participants' understanding of the relationship between environmental sanitation and stunting, with 75% of the mothers reaching a good level of knowledge after the session. This activity is expected to empower communities to prevent stunting through improved household sanitation practices.. Keywords: stunting, environmental sanitation, health education, mothers of toddlers, community service